Evolution of the construction of Dublin City Council's housing, with emphasis on wall construction. Issue 2 (11th May 2015) - O'Neill, Daniel; Gunnigan, Louis; Clarke, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present information on the construction technology used to build Dublin City Council's (DCC's) housing stock, with an emphasis on wall construction. Design/methodology/approach – The methodology applied was a mix of literature review and archival research. The research was undertaken as part of PhD research exploring the energy upgrade of a housing stock. Findings – The research uncovered details of the construction technology used in the construction of DCC's housing stock, especially wall construction. These details disprove perceptions and assumptions made on the evolution of construction technology in Dublin and Ireland. Research limitations/implications – The research is limited in that it primarily focused on the period between 1887 to the introduction of the 1991 Building Regulations. Further research is required on both DCC's housing stock and the Irish housing stock to identify the specific changes in construction technology. Practical implications – It is hoped this research will be a foundation for further research on the evolution of house construction technology, and housing stock asset intelligence in Ireland. Originality/value – This research provides information for researchers and professionals with an interest in the evolution of Irish house construction technology. This is an area which has not received significant attention in Irish built-environment research.